Post COVID-19 Multisystemic Inflammatory Syndrome Revealed by Seizures: A Case Report - Mebrouk, Nadia; Lachkar, Yasmine; Bentalha, Aziza; Chat, Latifa; Kriouile, Yamna; Alaoui, Asmaa Mdaghri (International Journal of Innovative Research in Medical Science, 2022)
The Covid-19 infection disrupts various organs, including the liver, kidney, and nervous system. Common neurological symptoms of the Covid-19 infection include delirium, confusion, headache, and loss of sense of smell and taste. In rare cases it can cause seizure. The virus enters the nervous system either directly through nerve pathways or indirectly through the ACE2 receptor. Understanding the potential mechanisms is necessary to gain better insight into COVID-19 induced seizure pathogenesis and to design the correct treatment strategies to achieve appropriate treatment for seizure and epilepsy. We report the case of a child with post covid syndrome with multisystemic inflammatory syndrome damage, and we explain the mechanisms of the damage to the nervous system.